The Companies Act 2016: Key Changes and Challenges - Shih, Lee (Journal of Malaysian and Comparative Law, 2018)
The Companies Act 2016 (2016 Act) has been brought into force in stages starting from 31 January 2017.1 To date all the provisions of the 2016 Act have come into force except for section 241 contained in Division 8 Part III of the 2016 Act on the registration of company secretaries and the corporate rescue mechanisms. The 2016 Act is a culmination of more than 10 years of Malaysia’s corporate law reform process. While there have been piecemeal amendments to the old Companies Act 1965 (1965 Act), the 2016 Act represents a fresh start and a modernisation of Malaysia’s corporate law framework. Before delving into the key changes contained in the 2016 Act, it is useful to look back at the corporate law reform process which led to the enactment of the 2016 Act.